Nutritional Targets for Modulation of the Microbiota in Obesity. Issue 6 (25th July 2013) - Pimentel, Gustavo D.; Micheletti, Thayana O.; Pace, Fernanda; Gurwitz, David
Abstract <table-wrap position="anchor" orientation="portrait"> <x xml:space="preserve">Table </x> Preclinical Research </table-wrap> The gut microbiota is being increasingly appreciated by both clinical and research professionals as the human ancestral genome has undergone modification by the microbes that colonize the human body. The gut is now known to be a key metabolic organ that contains some 15 000 bacterial species that influence health and chronic diseases, the latter including obesity, type 2 diabetes, hepatic steatosis, and hypertension. Based on the potentially beneficial effects of nutrients, this review discusses how obesity disturbs the gut microbiota. Additionally, the main dietary nutrients known to modulate the intestine microbiome were highlighted.